PENGARUH PROMOSI, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN MAKANAN DI GRILL FOOD STEAK 1838 JAMBI DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Amin, Rahmat Febriansyah; Indrawati, Mei (Jurnal Manajerial Bisnis, 2025)
This research was conducted to examine the influence of promotion, price, and service quality on purchasing decisions at Grill Food Steak 1838 Jambi through the intervening variable of purchase satisfaction. The study utilized a quantitative method with an associative causal research design. The sample consisted of 50 individuals selected from a population of 250 using systematic random sampling technique. Hypothesis testing was performed using SEM PLS version 4.1. Data collection employed questionnaire dissemination technique. The findings indicate that promotion does not have a significant effect on purchasing decisions, while price and service quality exhibit significant influence on purchasing decisions. Promotion does not affect consumer satisfaction with purchases, nor does price influence consumer satisfaction. However, service quality has a significant impact on consumer satisfaction. Consumer satisfaction, in turn, does not affect purchasing decisions. Neither promotion nor price through consumer satisfaction affect purchasing decisions, although service quality through consumer satisfaction does not influence purchasing decisions.